Effectiveness evaluation of Hazard Identification Support Method for Machine designers - HATA, Yukio; SAITO, Tsuyoshi (Journal of Occupational Safety and Health, 2024)
The implementation of risk assessment (hereafter, “RA”) at the design stage is essential for preventing workplace accidents related to the use of machines. However, among small and medium-sized machine manufacturers and in tegrators in particular, the dissemination and establishment of RA are impeded by the difficulty of performing “hazard identification” which is regarded as the most important step in the RA process. To establish an effective method for supporting machine designers who lack experience performing RA, the authors previously proposed a hazard identification support method based on the requirements stated in industrial standards related to machinery safety. This concept was inspired by the application of type-C machine safety standards to obtain a presumption of conformity with the applicable European directive(s), e.g., Machinery.This report describes the results of an effectiveness evaluation of the proposed support method on the basis of subjective impressions of 12 designers working at small and medium-sized machine manufacturers, with a prototype software tool designed to assist with the hazard identification process. The results indicate that the designers viewed the proposed support method favorably and that it was effective to a certain extent in providing support to inexperienced machine designers.